Natural Logic : a transdisciplinary method of analysis of cognition and language - Kohler, Alaric (My University, 2015)
Natural Logic provides a methodology of analysis for transdisciplinary research, particularly relevant for dialogical approaches of cognition, social interactions and communication based on discourse, and micro-scale analysis. This theory approaches thought and discourse as intertwined together, based on the idea that most thought processes used by adults are embodied in a vernacular language. Formal language are at the best a relevant model of such vernacular languages, and are based on a different logic. Grize developed Natural Logic as a non-formal logic for the study of natural reasoning, after working for Piaget's formal logic of meaning. In Natural Logic, discourse can be analyzed thanks to a set of thought operations, which define an open system for the description of meaning making. The discursive thought is approached as a whole, in such a way that logical operations remain linked with their content, with the language used by the interlocutors, and with the context of enunciation.  The system of thought operations is dynamic, focused on changes throughout the process of communication, and allows to study meaning across individual use of it, at various level of analysis such as the discursive thought of a pair of interlocutors, of a group, or at the level of social representations. This presentation will provide a quick introduction to the method of analysis, and short examples of results traced with Natural Logic. The results are drawn from educational practices, presenting for instance analysis of misunderstanding between students.
, 16th Biennal Conference of the International Society of Theoretical Psychology, Coventry, UK
Keywords: natural logic discourse analysis dialogic communication meaning-making semiotic